Taxpayers perception on electronic fiscal devices (EFDS): A case of Dar es salaam. - A dissertation submitted in partial fulfilment of the requirements for the award of Master of Business Administration (MBA) in Corporate Management of the Mzumbe University. (Mzumbe University, 2026)
A dissertation submitted in partial fulfillment of the requirements for the degree of Master of Corporate Management of Mzumbe University.